Kinetic and thermodynamic evaluation of azithromycin as a green corrosion inhibitor during acid cleaning process of mild steel using an experimental and theoretical approach - Alexander I. Ikeuba; Joseph E. Ntibi; Peter C. Okafor; Benedict I. Ita; Augustine U. Agobi; Fredrick C. Asogwa; Ben J. Omang; Ededet A. Eno; Hitler Loius; Stephen A. Adalikwu; Bamibola A. Abiola; Fidelis E. Abeng; et al. (Results in Chemistry, 2023)
Data from experiments and molecular computation were used to evaluate azithromycin as a safe and innocuous corrosion retardant for mild steel in acidic environments. Hydrogen evolution experiments were conducted between 303 and 333 K with and without azithromycin in hydrochloric acid solution. SEM photos and the results of hydrogen evolution demonstrate that azithromycin suppresses steel corrosion in an acidic environment. The inhibition efficiency (IE%) of azithromycin increases with the rise in concentration and the drop in temperature. The maximum IE% (81.36%) was obtained at 800 mg/L of azithromycin at 303 K. The corrosion reaction rates could be described with a first-order rate law. The range of thermodynamic parameters obtained from 303 K to 333 K for entropy (−181.2 to −91.9 J/mol), enthalpy (18.6 to 50.1 kJ/mol), and activation energy (21.2 to 52.7 kJ/mol) indicate the corrosion is spontaneous and endothermic. The results of the experiment agreed with the Langmuir model for adsorption, and physisorption is postulated for the adsorption of azithromycin on mild steel based on the ΔG values (−12.0 to −2.8 kJ/mol) which were below −20 kJ/mol. According to computational details, oxygen hetero atoms with relatively very large Mulliken charges are the most susceptible active locations for adsorption of Azithromycin on the metal surface.